Oxidations of pyrrolidines and piperidines to afford CH-functionalized isopropyl-1-carboxylate congeners. (13th April 2021) - Gunawan, Steven; Bedard, Nathan; Foley, Christopher; Hulme, Christopher
Graphical abstract: Highlights: One-pot oxidations affording α-hydroxy-β, β-dibromo carbamate protected. pyrrolidines and piperidines. Simple applications of molecular bromine affording N -acyliminium ion precursors. Novel hypervalent iodine or NBS/AIBN mediated one-pot processes. Abstract: This article describes the action of iodine(III) reagents [diacetoxyiodobenzene, PhI(OAc)2, and iodosobenzene, (PhIO)n ] in conjunction with TMSBr which act as functional bromine equivalents in unique oxidations of saturated, carbamate protected N -heterocycles. Interestingly, during this work, treatment of the same carbamates with molecular bromine alone afforded similar products, which were sequestered by the solvent methanol.